Understanding determinants of acute stroke thrombolysis using the tailored implementation for chronic diseases framework: a qualitative study - Lesli E. Skolarus; Gina M. Neshewat; Lacey Evans; Molly Green; Narmeen Rehman; Zach Landis-Lewis; Jillian Welsh Schrader; Anne E. Sales (BMC, 2019)
Abstract Background The Tailored Implementation in Chronic Disease (TICD) framework is a comprehensive framework describing the determinants of implementation success that has been used extensively in primary care settings. We explored the utility of the TICD to identify determinants of practice in an acute setting, namely guideline concordant acute stroke thrombolysis in a low-resourced, predominately minority serving, large, Emergency Department (ED). Methods Through workshops and expert review, we developed an interview guide informed by the TICD framework. We then conducted semi-structured interviews with data collected through written transcripts, audio transcripts or interviewer notes based on participant availability. Three independent coders then performed a content analysis using template analysis, but open to new determinants that arose from the data, into the TICD framework. Results We performed a total of 15 semi-structured interviews with ED acute stroke providers including medical technicians, nurses, and physicians. We found that guideline factors, individual health professional factors, and patient factors domains were barriers to guideline concordant acute stroke thrombolysis. The domain professional interactions was a facilitator to treatment. We identified three determinants, healthcare professional burnout, health care professional turnover and surrogate decision making, that are not part of the TICD framework. Conclusions Most determinants of acute stroke thrombolysis are included within the TICD framework. Inclusion of healthcare professional burnout, healthcare professional turnover and surrogate decision making may assist in expanding the TICD to time-sensitive ED conditions. Further work is needed to confirm this finding and to establish whether the TICD is applicable for use in non-time sensitive ED conditions. Interventions that address guideline, individual health professional and patient factors may improve guideline concordant acute stroke thrombolysis.